Does soccer headgear reduce the incidence of sport-related concussion? A cluster, randomised controlled trial of adolescent athletes - McGuine, T.; Post, E.; Pfaller, A. Y.; Hetzel, S.; Schwarz, A.; Brooks, M. A.; Kliethermes, S. A. (British Journal of Sports Medicine, 2020)
BACKGROUND: There have been no large randomised controlled trials to determine whether soccer headgear reduces the incidence or severity of sport-related concussion (SRC) in US high school athletes. OBJECTIVE: We aimed to determine whether headgear reduces the incidence or severity (days out from soccer) of SRCs in soccer players. METHODS: 2766 participants (67% female, age 15.6±1.2) (who undertook 3050 participant years) participated in this cluster randomised trial. Athletes in the headgear (HG) group wore headgear during the season, while those in the no headgear (NoHG) group did not. Staff recorded SRC and non-SRC injuries and soccer exposures. Multivariate Cox proportional hazards models were used to examine time-to-SRC between groups, while severity was compared with a Wilcoxon rank-sum test. RESULTS: 130 participants (5.3% female, 2.2% male) sustained an SRC. The incidence of SRC was not different between the HG and NoHG groups for males (HR: 2.00 (0.63-6.43) p=0.242) and females (HR: 0.86 (0.54-1.36) p=0.520). Days lost from SRC were not different (p=0.583) between the HG group (13.5 (11.0-018.8) days) and the NoHG group (13.0 (9.0-18.8) days). CONCLUSIONS: Soccer headgear did not reduce the incidence or severity of SRC in high school soccer players.